Digestive health with REAL food : a bigger, better practical guide to an anti-inflammatory, nutrient-dense diet for IBS & other digestive issues - Jacob, Aglaée (Paleo Magazine, 2018)
Health begins in the gut. In addition to digestive disorders, many other health problems can stem from damage to your intestines, so tackling your digestion is crucial if you want to maximize your chances of obtaining optimal health, The information in "Digestive Health with REAL Food" will teach you how to address the root causes of your digestive troubles, and will help you build your own optimal diet by identifying the best foods for your digestive system: ones that are easy to digest, anti-inflammatory, nutrient-dense, healing, and low in irritants and allergens. The nutritional protocol in this book, developed by registered dietitian Aglaée Jacobs, addresses numerous digestive problems, including: irritable bowel syndrome (IBS), Crohn's disease, Ulcerative colitis, Small intestinal bacterial overgrowth (SIBO), Fructose malabsorption, FODMAP intolerance, Gastroesophageal reflux disease (GERD), Gallbladder issues, Abnormal intestinal permeability (leaky gut), Gut dysbiosis (gut flora imbalance), Celiac disease, Non-celiac gluten sensitivity, multiple food sensitivities, and many more ... In addition to guiding you on how to successfully follow an elimination diet, Aglaée will teach you everythng you need to know about dietary supplements, stress management, eating out and travel strategies, as well as how to troubleshoot various digestive problems. This updated and expanded second edition includes over 50 recipes, each accompanied by a stunning color photograph, meal and snack ideas, helpful charts, food lists and weekly meal plans, and a wealth of new information to get you started on the path to better digestion. -- back cover.